RESULTS OF RESEARCH ON AN IMPROVED COTTON REGENATOR - ROZMETOV, RAKHMATJON (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article presents the results of the research conducted on the application of the improved cotton regenerator to the Independence cotton cleaning technology. In the studies, the length uniformity index of cotton fiber (Unf), relative breaking strength - hardness (Str), the number of impurities of cotton fiber (Cnt), the amount of short fibers (SFI), the index of contamination with non-fiber impurities (T) of the technology installed in the enterprise were determined and changes in fiber quality indicators such as yellowness (+b) were investigated. According to the results of the conducted research, it was found that the quality indicators of cotton fiber produced in the improved cotton regenerator are better than the existing cotton regenerator.